2023
DOI: 10.1037/pspp0000455
|View full text |Cite
|
Sign up to set email alerts
|

What social lives do single people want? A person-centered approach to identifying profiles of social motives among singles.

Abstract: Despite the worldwide increase in unpartnered individuals (i.e., singles), little research exists to provide a comprehensive understanding of the heterogeneity within this population. In the present research (N = 3,195), we drew on the fundamental social motives framework to provide a theory-based description and understanding of different “types” of single individuals. Across two Western samples (primarily European and American) and one Korean sample (all collected during the COVID-19 pandemic in 2020–2021), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Some readers may observe that our 6-profile solution for singles differs from the 10profile solution found by Walsh et al, 2022 and the 3-profile solution found by Park et al, 2023. These variations likely stem from the fact that LPA results hinge on the particular indicator variables entered into the model (Ferguson et al, 2020).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Some readers may observe that our 6-profile solution for singles differs from the 10profile solution found by Walsh et al, 2022 and the 3-profile solution found by Park et al, 2023. These variations likely stem from the fact that LPA results hinge on the particular indicator variables entered into the model (Ferguson et al, 2020).…”
Section: Discussionmentioning
confidence: 54%
“…As for Park et al, 2023, the researchers used an entirely different set of social motive indicator variables, which unsurprisingly led to a distinct profile solution. When conducting LPA, researchers pick indicator variables to serve a particular purpose, and different indicators often create different profile solutions (Ferguson, 2009; Spurk et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, drawing on the fundamental social motives framework, Park, MacDonald, Impett, et al. (2023) identified three groups of singles with relatively consistent motivational patterns across three samples: (a) singles with strong independence motives and little interest in affiliation, mating, or status; (b) singles with considerable interest in self‐protection as well as social connections and status; and (c) singles with little interest in self‐protection or independence but moderate interest in affiliation. These groups differed not only in general well‐being outcomes but also in (self‐reported) behavioral outcomes.…”
Section: Within‐group Investigation Of Singles: Differences Among Sin...mentioning
confidence: 99%